Comprehensive Profiling of Diverse Genetic Reporters with Application to Whole-Cell and Cell-Free Biosensors - Lopreside, Antonia (Anal Chem, 2019)
[Image: see text] Whole-cell and cell-free transcription-translation biosensors have recently become favorable alternatives to conventional detection methods, as they are cost-effective, environmental friendly, and easy to use. Importantly, the biological responses from the biosensors need to be converted into a physicochemical signal for easy detection, and a variety of genetic reporters have been employed for this purpose. Reporter gene selection is vital to a sensor performance and application success. However, it was largely based on trial and error with very few systematic side-by-side investigations reported. To address this bottleneck, here we compared eight reporters from three reporter categories, i.e., fluorescent (gfpmut3, deGFP, mCherry, mScarlet-I), colorimetric (lacZ), and bioluminescent (luxCDABE from Aliivibrio fischeri and Photorhabdus luminescens, NanoLuc) reporters, under the control of two representative biosensors for mercury- and quorum-sensing molecules. Both whole-cell and cell-free formats were investigated to assess key sensing features including limit of detection (LOD), input and output dynamic ranges, response time, and output visibility. For both whole-cell biosensors, the lowest detectable concentration of analytes and the fastest responses were achieved with NanoLuc. Notably, we developed, to date, the most sensitive whole-cell mercury biosensor using NanoLuc as reporter, with an LOD ≤ 50.0 fM HgCl(2) 30 min postinduction. For cell-free biosensors, overall, NanoLuc and deGFP led to shorter response time and lower LOD than the others. This comprehensive profile of diverse reporters in a single setting provides a new important benchmark for reporter selection, aiding the rapid development of whole-cell and cell-free biosensors for various applications in the environment and health.